Climate change impact on the cost of decarbonisation in a hydro-based power system. (1st May 2022) - Suomalainen, Kiti; Wen, Le; Sheng, Mingyue Selena; Sharp, Basil
Abstract: Understanding the impact of climate change on renewable energy resources is increasingly vital as our energy systems transition towards higher levels of renewable generation. This paper explores power system transition under climate change impacts on hydro resources, as well as the impact of climate change on the cost of decarbonisation. An integrated energy systems assessment tool is used to investigate the impact of altered seasonal availability factors on the optimal energy investment pathways. The cost of decarbonisation is assessed under climate change impact on the hydro resources, as well as the impact of discount rate assumptions on the total cost of decarbonisation. Results show that in the case of New Zealand, more hydro will be available in winter due to climate change, but less in summer, which is compensated for with increased solar capacity. Decarbonisation in New Zealand sees a major transformation in the transport sector, supported by a relatively moderate increase in overall demand in the electricity sector. While climate change impact on the hydro resource may reduce the total cost of decarbonisation in New Zealand, this cannot be generalised, as these impacts vary across countries and regions. Highlights: Climate change amplifies seasonal availability of hydro in New Zealand. Climate change has indirect effects on optimal long-term energy system investments. Cost of decarbonisation decreases slightly due to climate change in New Zealand. Trade-off between solar and wind to support hydro under climate change.